Reduction of health care–associated infection indicators by copper oxide–impregnated textiles: Crossover, double-blind controlled study in chronic ventilator-dependent patients - Marcus, Esther-Lee; Yosef, Hana; Borkow, Gadi; Caine, Yehezkel; Sasson, Ady; Moses, Allon E. (American journal of infection control, 2017)
•We investigated the effect of copper oxide–impregnated textiles in reducing nosocomial infection-related indicators.•The study subjects were mechanically ventilated patients in long-term care wards.•The design was a crossover, double-blind controlled study.•Using these biocidal textiles resulted in reduction in antibiotic utilization and fever days.•Biocidal textiles may be a supplementary measure aimed at reducing the rate of health care–associated infections. [Display omitted] Copper oxide has potent wide-spectrum biocidal properties. The purpose of this study is to determine if replacing hospital textiles with copper oxide–impregnated textiles reduces the following health care–associated infection (HAI) indicators: antibiotic treatment initiation events (ATIEs), fever days, and antibiotic usage in hospitalized chronic ventilator-dependent patients. A 7-month, crossover, double-blind controlled trial including all patients in 2 ventilator-dependent wards in a long-term care hospital. For 3 months (period 1), one ward received copper oxide–impregnated textiles and the other received untreated textiles. After a 1-month washout period of using regular textiles, for 3 months (period 2) the ward that received the treated textiles received the control textiles and vice versa. The personnel were blinded to which were treated or control textiles. There were no differences in infection control measures during the study. There were reductions of 29.3% (P = .002), 55.5% (P < .0001), 23.0% (P < .0001), and 27.5% (P < .0001) in the ATIEs, fever days (>37.6°C), days of antibiotic treatment, and antibiotic defined daily dose per 1,000 hospitalization days, respectively, when using the copper oxide–impregnated textiles. Use of copper oxide–impregnated biocidal textiles in a long-term care ward of ventilator-dependent patients was associated with a significant reduction of HAI indicators and antibiotic utilization. Using copper oxide–impregnated biocidal textiles may be an important measure aimed at reducing HAIs in long-term care medical settings.